Câu hỏi
Đạo hàm của hàm số \(y = \dfrac{{{x^4}}}{2} + \dfrac{{5{x^3}}}{3} - \sqrt {2x} + {a^2}\) (a là hằng số) bằng:
- A \(2{x^3} + 5{x^2} - \dfrac{1}{{\sqrt {2x} }} + 2a\)
- B \(2{x^3} + 5{x^2} + \dfrac{1}{{2\sqrt {2x} }}\)
- C \(2{x^3} + 5{x^2} - \dfrac{1}{{\sqrt {2x} }}\)
- D \(2{x^3} + 5{x^2} - \sqrt 2 \)
Phương pháp giải:
Sử dụng công thức tính đạo hàm \(\left( {{x^n}} \right)' = n{x^{n - 1}},\,\,\left( {\sqrt x } \right)' = \dfrac{1}{{2\sqrt x }}\).
Lời giải chi tiết:
\(y' = 2{x^3} + 5{x^2} - \dfrac{2}{{2\sqrt {2x} }} = 2{x^3} + 5{x^2} - \dfrac{1}{{\sqrt {2x} }}\).
Chọn C.